2017
DOI: 10.3892/ijo.2017.4198
|View full text |Cite
|
Sign up to set email alerts
|

High expression of MAGE-A9 contributes to stemness and malignancy of human hepatocellular carcinoma

Abstract: MAGE-A9, a well-characterized cancer testis antigen (CTA), belongs to a member of melanoma antigen gene (MAGE) family. In human malignancies, aberrant expression of MAGE genes correlated with poor clinical prognosis, increased tumor growth, metastases, and enrichment in stem cell populations of certain cancers. Cancer stem cells (CSCs) have been proposed to contribute to the major malignant phenotypes of liver cancer, including recurrence, metastasis and chemoresistance. However, expression and potential role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…MAGE-A9, a member of the MAGE-A gene family, is frequently expressed in various human tumors (Gu et al, 2014). MAGE-A9 contributes to malignant biological phenotypes, including cell proliferation, chemoresistance and migration of EpCAM + HCC cells (Wei et al, 2018).…”
Section: Rack1 Tg737 and Mage-a9mentioning
confidence: 99%
“…MAGE-A9, a member of the MAGE-A gene family, is frequently expressed in various human tumors (Gu et al, 2014). MAGE-A9 contributes to malignant biological phenotypes, including cell proliferation, chemoresistance and migration of EpCAM + HCC cells (Wei et al, 2018).…”
Section: Rack1 Tg737 and Mage-a9mentioning
confidence: 99%
“…Subsequently, Youping Wei [45] found that high expression of MAGEA9 contributes to stemness and malignancy of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that MAGEA9 expression is a valuable prognostic biomarker for HCC and high MAGEA9 expression suggests unfavorable survival outcomes in HCC patients. Subsequently, Youping Wei [45] found that high expression of MAGEA9 contributes to stemness and malignancy of HCC.…”
Section: Discussionmentioning
confidence: 99%